2013
DOI: 10.1002/wrcr.20079
|View full text |Cite
|
Sign up to set email alerts
|

Links between soil properties and steady‐state solute transport through cultivated topsoil at the field scale

Abstract: [1] It is known that solute transport through soil is heterogeneous at all spatial scales. However, little data are available to allow quantification of these heterogeneities at the field scale or larger. In this study, we investigated the spatial patterns of soil properties, hydrologic state variables, and tracer breakthrough curves (BTCs) at the field scale for the inert solute transport under a steady-state irrigation rate which produced near-saturated conditions. Sixty-five undisturbed soil columns approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 69 publications
7
35
1
Order By: Relevance
“…normalλapp=normalμ2L/2normalμ12 where μ 2 is the second central temporal moment or variance, σ 2 , of the pdf; L is the length of the sample; and μ 1 is the normalized first moment of the pdf. See Koestel et al (2012) for a detailed description of modeling breakthrough curves and calculation of apparent dispersivity.…”
Section: Methodsmentioning
confidence: 99%
“…normalλapp=normalμ2L/2normalμ12 where μ 2 is the second central temporal moment or variance, σ 2 , of the pdf; L is the length of the sample; and μ 1 is the normalized first moment of the pdf. See Koestel et al (2012) for a detailed description of modeling breakthrough curves and calculation of apparent dispersivity.…”
Section: Methodsmentioning
confidence: 99%
“…The content of organic matter was also, in this study, hypothesized to reduce preferential flow as was found by Jarvis et al (2007). Koestel et al (2013) found a positive correlation between preferential flow and the degree of water saturation. The time for 5% breakthrough (T 5 ) of an applied dissolved nonreactive tracer has also been used as an indicator for preferential flow Norgaard et al, 2013).…”
mentioning
confidence: 89%
“…The parameterization of the double log-normal distribution functions was conducted with R software (version 2.14.1) closely following the procedure provided in Koestel et al (2013). In brief, the measured BTC data points (f(t)) were first discretized to a temporal resolution of 2 min by linear interpolation.…”
Section: Tritium Breakthrough Experimentsmentioning
confidence: 99%
“…Koestel et al (2012) reported a negative correlation between bulk density (BD) and the magnitude of preferential flow and transport based on analysis of 733 breakthrough curves (BTC). More recently, Koestel et al (2013) reported that the extent of preferential transport was positively correlated to BD and the degree of water saturation.…”
mentioning
confidence: 98%